Strategi Komunikasi Pusat Informasi Dan Konseling Remaja (PIK R) Merpati Pada Program Generasi Berencana Di SMKN 3 Kota Bengkulu - Syafira, Girana Dea; Narti, Sri; Sari, Sapta (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The Genre program is a forum for developing national character because it teaches adolescents to stay away from early marriage, premarital sex and narcotics. The research aims to find out the Communication Strategy of the Youth Information and Counseling Center (PIK R) Merpati on the Generation Planning Program at SMKN 3 Bengkulu City.The method used in this research is qualitative research. This research uses Everett M. Rogers' innovation diffusion communication model which consists of: The results showed that first, PIK R Merpati SMKN 3 Bengkulu City provided knowledge on the importance of maintaining adolescent reproductive health only by conducting direct socialization during student orientation (MOS) for students of SMKN 3 Bengkulu City, namely through regular meetings to PIK R Merpati members. Furthermore, knowledge is also carried out by indirect socialization through the Instagram account @pikrmerpatismkn3. Second, the persuasion of PIK R Merpati trainers is by giving appreciation to students in the form of gifts for being active in the education of maintaining adolescent reproductive health. The socialization media used by PIK R Merpati is by disseminating videos and pamphlets on social media Instagram account @pikrmerpatismkn3 such as animations, and cartoons. Third, the decision of students of SMKN 3 Bengkulu City is that the majority accept it while only one student rejects it. Fourth, Confirmation of students of SMKN 3 Bengkulu City accepts well the education of maintaining adolescent reproductive health on the grounds that they consider the information important. While students who reject education because they do not get permission from their parents. The Communication Strategy of the Merpati Youth Information and Counseling Center (PIK R) on the Generasi Berencana Program at SMKN 3 Bengkulu City has been running well but has not been fully maximized because the number of followers of PIK R Merpati participants has not shown a significant increase in the number of followers of PIK R activities each year, because the communication strategy focuses more on face-to-face socialization while socialization through media only Instagram accounts should involve more social media as a medium of education.